Virtual laboratories in chemical and laboratory safety education - Girmay, Samuel (LUMAT-B: International Journal on Math, Science and Technology Education, 2023)
We present a next-generation web-based 360° virtual laboratory safety training which a mandatory training for all the students and staff members in Aalto chemical engineering department. We collected feedback from the students and staff members in Aalto University School of Chemical Engineering and University of Eastern Finland. The feedback of training was highly positive. In the open feedback, students reported significant decrease of anxiety and stress as well as better understanding different aspects of chemical and laboratory safety. Overall, results indicate that the virtual laboratory is effective and efficient tool for laboratory and chemical safety training.